UNIFORM CHARAKTERIZING ASPECTS AND DESIGN DEVELOPMENT CONDITIONS - Mežinska, Silvija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The topicality of the research is based on Latvian Interior system officials everyday uniform non-compliance with modern requirements. The aim of the article is to determine uniform characterizing elements and design development conditions, based on the theoretical study of uniforms in modern context. The methods of research: theoretical – investigation and analysis of relevant literature, internet resources and regulatory documents. Empirical – methods of data collecting and processing: case study criteria analysis, focus-group discussions, expert interviews. Research base: 36 respondents of Ministry of the Interior system, 4 experts; period of the research 2015-2016. The research has practical meaning, because it it is based on current situation research, meeting with the uniform users, discussing reasons of dissatisfaction with the current uniform, which provides uniform requirements for clothing designer. Results of the research support the choice of evaluation criteria for the analogue evaluation, and determines groups of criteria for evaluation of the developed design samples.